Erratum to “High Conductive Copolymers of Polypyrrole-α,ω-Diamine Polydimethylsiloxane [European Polymer Journal 42(2006) (2361–2368)] - Kızılcan, Nilgün; Öz, Nesrin Köken; Ustamehmetoğlu, Belkıs; Akar, Ahmet (Elsevier BV, 2009)
Blank1 (PPy) – 0.01 0.232 1.3 5 i i Blank2 (PPy) – 0.05 0.47 2 21 i i 1 0.034 0.022 0.232 – 24 s s 2 0.034 0.05 0.232 2 10 5 48 s s 3 0.034 0.15 0.232 4 10 5 80 s s 4 0.0034 0.05 0.232 1 31 i i 5 0.0034 0.025 0.470 0.1 9 i i 6 0.0034 0.05 0.470 1.8 18 i i 7 0.0034 0.075 0.470 2 23 i i 8 0.0034 0.10 0.470 1.1 28 i i 9 0.0034 0.15 0.470 0.2 17 i i 10 0.0034 0.23 0.470 0.1 12 i i The authors regret that the above paper Table 1 and Fig. 6 were prepared incorrectly due to the wrong measurements. The updated Table 1 and Fig. 6 are reproduced correctly below.